THE STRUCTURE OF MUTUAL RELATIONS OF MARKET AND GOVERMENT IN MODERN SOCIETY - Мірошниченко, Г.О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
Co-operation of power and market in the transformed society is analysed in the article. Logic of functioning of economic sector of public life in the modern world, control techniques, used by government are studied. During the study were considered the tax system, mechanisms of control and allocation of resources, corruption in post-soviet countries.